AUTOMATIC TESTING FRAMEWORK BASED ON SERENITY AND JENKINS AUTOMATED BUILD - Umi Sa'adah; Jauari Akhmad Nur Hasim; Andhik Ampuh Yunanto; Desy Intan Permatasari; Fadilah Fahrul Hardiansyah; Irma Wulandari; Hazna At Thooriqoh (JUTI: Jurnal Ilmiah Teknologi Informasi, 2021)
Software Testing plays an important role in making high quality products and the right time. The process of testing done manually is often inaccurate, unreliable, and needed more than automatic testing. This research proposes a new framework for automation testing. This framework will help developers to create applications with better quality and shorten testing time. This framework offers a solution for developers so that the testing process is carried out easily and quickly. Our proposed concept consists of an automated test script based on Serenity Framework and can be done as a background process using Jenkins. Input of the system is a testing scenario, then mapped into Java Programming Language. Output of this system are test reports that represent the scenario that has been carried out. the results of implementation system prove that developers are helped by this framework in the software testing process. So that in this study it can be concluded that the automated testing framework that has been developed can improve the quality of application products through effective and efficient work methods.